2014
DOI: 10.3390/f5092106
|View full text |Cite
|
Sign up to set email alerts
|

Belowground Competition Directs Spatial Patterns of Seedling Growth in Boreal Pine Forests in Fennoscandia

Abstract: Aboveground competition is often argued to be the main process determining patterns of natural forest regeneration. However, the theory of multiple resource limitation suggests that seedling performance also depends on belowground competition and, thus, that their relative influence is of fundamental importance. Two approaches were used to address the relative importance of above-and below-ground competition on regeneration in a nutrient-poor pine (Pinus sylvestris) boreal forest. Firstly, seedling establishme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Noguchi and Yoshida 2004;Donoso and Nyland 2005;Nilsson and Wardle 2005;Bose et al 2014;Dodson et al 2014). In these forests, regeneration of desirable tree species (especially, but not limited to shade-intolerant species) may be poor or delayed for years or even decades (Hibbs and Bower 2001;Axelsson et al 2014).…”
Section: Ecological Challengesmentioning
confidence: 99%
“…Noguchi and Yoshida 2004;Donoso and Nyland 2005;Nilsson and Wardle 2005;Bose et al 2014;Dodson et al 2014). In these forests, regeneration of desirable tree species (especially, but not limited to shade-intolerant species) may be poor or delayed for years or even decades (Hibbs and Bower 2001;Axelsson et al 2014).…”
Section: Ecological Challengesmentioning
confidence: 99%
“…Because the effect of browsing was minor, the reasons are likely related to the competitive environment in the gaps. Due to the shadeintolerance of pine and birch, it is apparent that their niche requirements are not met in small canopy gaps, particularly in nutrient-poor soils in which the competition for belowground resources also plays an important role (Björkman and Lundeberg 1971;Axelsson et al 2014).…”
Section: Main Results and Discussionmentioning
confidence: 99%
“…Consequently, gap size was found to be crucial in initiating forest regeneration. Earlier work in boreal Scots pine forests in northern Sweden found that competition for nutrients is crucial [16,48], while studies in temperate Norway spruce stands highlighted the importance of light for successful regeneration [49]. In boreal Norway spruce single-tree selection forests of central Sweden, no relationship between seedling occurrence and canopy gaps was found [50].…”
Section: Regeneration Establishmentmentioning
confidence: 98%